2012
DOI: 10.1143/jpsj.81.024705
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Magnetoresistance Effects in Fe, Co, Ni, Fe4N, and Half-Metallic Ferromagnet: A Systematic Analysis

Abstract: We theoretically analyze the anisotropic magnetoresistance (AMR) effects of bcc Fe (þ), fcc Co (þ), fcc Ni (þ), Fe 4 N (À), and a half-metallic ferromagnet (À). The sign in each parenthesis represents the sign of the AMR ratio observed experimentally. We here use the two-current model for a system consisting of a spin-polarized conduction state and localized d states with spin-orbit interaction. From the model, we first derive a general expression of the AMR ratio. The expression consists of a resistivity of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
203
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(212 citation statements)
references
References 44 publications
9
203
0
Order By: Relevance
“…The calculated values of S and α are shown in the inset of Very recently, Kokado et al [18] have systematically investigated the sign of the anisotropy magnetoresisetnce (AMR) of ferromagnetic materials. As a result, they found that, for half-metallic ferromagnets, the dominant scattering is s↑→d↑or s↓→d↓, which cause the sign of the AMR tends to be negative [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The calculated values of S and α are shown in the inset of Very recently, Kokado et al [18] have systematically investigated the sign of the anisotropy magnetoresisetnce (AMR) of ferromagnetic materials. As a result, they found that, for half-metallic ferromagnets, the dominant scattering is s↑→d↑or s↓→d↓, which cause the sign of the AMR tends to be negative [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Existing theoretical approaches to the AMR in metals and alloys are based on inclusion of the SO interaction in the lowest-order perturbation expansion. 42,47,48 However, the validity of such schemes for the Ni-rich alloys is limited due to the well-known fact that the SO interaction increases the resistivity by a factor of two or more as compared to the resistivity within the two current model.…”
Section: A Amr In Random Fcc Ni-based Alloysmentioning
confidence: 99%
“…Anisotropic magnetoresistance (AMR) is a direct consequence of s-d scattering in ferromagnets and is very sensitive to the distribution of the density of states at the Fermi energy [6], taking on a negative value for half metals [7]. AMR was explained by Smit [8] by the introduction of the spin-orbit interaction (SOI) through a perturbation that is suggested to result in an unequal distribution of d states, such that there exists more orbitals parallel to the magnetization rather than perpendicular to it, resulting in a shorter and longer mean-free path, respectively.…”
Section: Introductionmentioning
confidence: 99%